An investigation of microstructure and mechanical properties of malleable cast iron using metal casting process - Geetha, Muniandy (2010)
This thesis deals with the investigation of microstructure and mechanical properties of malleable cast iron using metal casting process. The objective of this thesis is to investigate the influence of different annealing rate to the mechanical properties and microstructure of malleable cast iron. The thesis describes the proper sand casting process in order to investigate the effect on microstructure and mechanical properties of malleable cast iron. The CO2 sand was used as the mould and pig iron as the raw material to produce malleable iron in this thesis. The studies of mechanical properties that are involved in this thesis consists of hardness, tensile strength, percent of elongation, carbon content, and the composition of malleable iron before and after metal casting process. Three different annealing rate was used in order to determine the correlation between mechanical properties and microstructure of malleable cast iron. As result, we observed that as the annealing rate increases, ductility of the samples also increased but compromising with hardness and strength. The microstructure shows graphite nodules in the samples , however it decreases the strength and percent of elongation. As for the recommendation, the mechanical properties including the wear, corrosion resistance, impact resistance, and noise reduction should be considered in order to optimally select a material for its specific application.